Evaluation of the Operational Budget Variance and Its Impact on Financial Performance at BRC Bar & Restaurant - K F Andriani; I W Karman; I M Sudana (Jurusan Akuntansi Politeknik Negeri Bali, 2019)
This research aims to determine 1) Effectiveness of operational budget implementation in 2017 at BRC Bar & Restaurant. 2) Efficiency of operational budget implementation in 2017 at BRC Bar & Restaurant. 3) The impact of the budget variance on the financial performance of 2017 at BRC Bar & Restaurant. This research used primary data that is the form of tolerance limits deviations, effectiveness and efficiency criteria, and cost percentage, and also used secondary data, that is operational budget reports, item sales report of food and beverages in 2017, quantity and price of food and beverage that obtained from BRC Bar & Restaurant through interview and documentation. Analysis techniques that used in this research are quantitative analysis technique by calculating the ratio of effectiveness, ratio of efficiency, variance analysis, and profitability ratio and also used descriptive qualitative technique which explains the cause of variance and the impact of budget variance to financial performance. The results show that the effectiveness level of operational budget implementation in 2017 is still less effective, because it has a ratio below 90,01% caused by the variance in operating income and for the efficiency level of operational budget implementation is still less efficient because it has a ratio above 65,01% due to the variance in operational costs. The difference in operational budget that occurs affects the decreased financial performance seen from profitability ratios. This shows that the implementation of the operational budget that has been arranged is still not going well.